TEACHING PREFIXES AS PART OF TEACHING VOCABULARY BY USING FLIP-A-CHIP TO THE ELEVENTH GRADE STUDENTS OF SENIOR HIGH SCHOOL AISYIYAH 1 OF PALEMBANG - M. Bambang Purwanto (Universitas PGRI Palembang, 2020)
Abstract.Â The main problem of this study was â€œis it effective to use flip-a-chip in teaching prefixes as part of teaching vocabulary to the eleventh grade students of senior high school Aisyiyah 1 of Palembang ?â€. The objective of this study was to find out whether or not flip-a-chip to teach prefixes as part of teaching vocabulary to the eleventh grade students of senior high school Aisyiyah 1 of Palembang. In this study the writer used experimental method. The population was the eleventh grade students of senior high school Aisyiyah 1 of Palembang. The samples were 32 students taken from the population of 202 students. In collecting data, the writer used a written test by using multiple choice test. The data were analyzed based on the result of pretest and posttest by using matched t-test formula. The mean score of the students in pretest was 66.95. The mean score of the students in posttest was 75.87. The effectiveness of this study was proved by the result of the calculation of matched t-test, which showed t-obtained (8.796) was higher than t-table (1.694). the alternative hypothesis (Ha) was accepted and consequently the null hypothesis (Ho) was rejected. In other words, it can be concluded that teaching the eleventh grade studentsâ€™ English prefixes by using flip-a-chip was effective.Key Words: Teaching, Prefixes, Vocabulary, and Flip-A-Clip